Separator, non-aqueous electrolyte secondary battery and battery pack including the same

JP7638204B2Active Publication Date: 2025-03-03PRIME PLANET ENERGY & SOLUTIONS INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021208540
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-12-22
Publication Date
2025-03-03
Estimated Expiration
2041-12-22

AI Technical Summary

Benefits of technology

【0014】 また、本開示により、複数の単電池が相互に電気的に接続されて配列された組電池であって、上記複数の単電池のうち少なくとも1つがここで開示される非水電解液二次電池である組電池が提供される。かかる構成によれば、充放電の繰り返しに伴う電極体の膨張圧力に対する反力の増加が低減されるため、組付け安定性が向上した組電池が実現される。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638204000003
    Figure 0007638204000003
  • Figure 0007638204000004
    Figure 0007638204000004
  • Figure 0007638204000005
    Figure 0007638204000005
Patent Text Reader

Abstract

To provide a separator which can reduce a reaction force against a pressure of expansion of an electrode body accompanying repetition of charge / discharge.SOLUTION: A separator disclosed herein comprises a base material 72 and an adhesive layer 76. The adhesive layer 76 is partially provided on one or both sides of the base material 72. Supposing that an initial thickness of the separator is T0, a thickness of the separator when a pressure of 1 MPa is applied to the separator in the state of being impregnated in an electrolyte solution 90 from a thickness direction of the separator is T1, a thickness of the separator when the pressure is reduced to 0.5 MPa after one-hour continuous application of 2 MPa-pressure to the separator from the thickness direction, subsequently to determination of the thickness T1 is T2, and a thickness of the separator when further subsequently to determination of the thickness of T2, a pressure of 4 MPa is applied to the separator from the thickness direction thereof and the pressure application is kept for 48 hours is T4, the following expressions (1) to (3) all hold: (1)1≤T1 / T0≤1.1; (2)0.92≤T2 / T1≤1; and (3)0.6≤T4 / T1≤0.8.SELECTED DRAWING: Figure 9
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator. The present invention also relates to a nonaqueous electrolyte secondary battery and a battery pack including the separator. [Background technology]

[0002] 2. Description of the Related Art Nonaqueous electrolyte secondary batteries such as lithium ion secondary batteries are suitable for use as portable power sources for personal computers, mobile terminals, etc., and as power sources for driving vehicles such as electric vehicles (BEVs), hybrid electric vehicles (HEVs), and plug-in hybrid electric vehicles (PHEVs), etc.

[0003] In one example of a nonaqueous electrolyte secondary battery, the nonaqueous electrolyte secondary battery includes an electrode body, a nonaqueous electrolyte, and a battery case that contains the electrode body and the nonaqueous electrolyte. The nonaqueous electrolyte secondary battery is used in the form of an assembled battery in which, for example, a plurality of single cells are stacked and arranged, and a predetermined pressure (hereinafter also referred to as "assembly pressure") is applied by a restraining member to the assembled battery. Typically, the assembled battery is initially charged and discharged in a state in which the assembly pressure is applied. At this time, the electrode body included in the nonaqueous electrolyte secondary battery expands and contracts with charging and discharging. In addition, since various reactions such as expansion of the active material and formation of a coating on the surface of the active material occur due to the initial charging and discharging, the internal pressure of the electrode body is higher after the initial charging than before the initial charging and discharging. That is, after the initial charging and discharging, a pressure is generated in which the electrode body pushes the battery case from the inside to the outside, and a counter force (hereinafter also referred to as "Beginning-of-Life counterforce") against this pressure is generated.

[0004] In addition, by repeatedly charging and discharging a nonaqueous electrolyte secondary battery, the thickness of the negative electrode increases, and the expansion pressure of the electrode body increases with repeated charging and discharging. As the expansion pressure of the electrode body increases, the reaction force against it also increases, so that the pressure generated on the electrode body increases, and deterioration of battery performance and shortening of battery life are likely to occur. One method for reducing the reaction force against the expansion pressure of the electrode body is to reduce the assembly pressure of the battery pack, but reducing the assembly pressure reduces the BOL reaction force, which leads to a trade-off in that the assembly stability of the battery pack deteriorates. Therefore, a technology for appropriately controlling the reaction force against the expansion pressure of the electrode body is required. As such a technology, for example, Patent Document 1 discloses a technique of arranging a non-foamed elastic sheet between the electrode body and the battery case. In addition, Patent Documents 2 to 4 disclose a separator configuration that can control the pressure of the electrode body. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 6865379 specification [Patent Document 2] JP 2013-222510 A [Patent Document 3] Patent No. 5799499 specification [Patent Document 4] Patent No. 5328034 specification Summary of the Invention [Problem to be solved by the invention]

[0006] According to the inventor's research, it was found that there is room for further improvement in the technology for reducing the increase in the reaction force against the expansion pressure of the electrode assembly caused by repeated charging and discharging. By reducing the increase in the reaction force against the expansion pressure of the electrode assembly caused by repeated charging and discharging, it becomes easier to adjust the assembly pressure of the battery pack, and productivity can be improved.

[0007] The present invention has been made in view of the above circumstances, and has as its main object to provide a separator that reduces an increase in reaction force against the expansion pressure of an electrode assembly caused by repeated charging and discharging of a nonaqueous electrolyte secondary battery. Another object of the present invention is to provide a nonaqueous electrolyte secondary battery and a battery pack including the separator. [Means for solving the problem]

[0008] The separator disclosed herein includes a sheet-like substrate made of a porous resin and an adhesive layer containing an adhesive resin, and the adhesive layer is partially provided on one or both sides in the thickness direction of the substrate. When the initial thickness of the separator is T0, the separator is impregnated with an electrolytic solution and a pressure of 1 MPa is applied to the separator in the thickness direction of the separator is T1, a pressure of 2 MPa is then applied to the separator in the thickness direction of the separator for one hour and the pressure is then reduced to 0.5 MPa is T2, and a pressure of 4 MPa is then applied to the separator in the thickness direction of the separator and the pressure is maintained for 48 hours is T4, the following formulas (1) to (3): (1) 1≦T1 / T0≦1.1 (2) 0.92≦T2 / T1≦1 (3) 0.6≦T4 / T1≦0.8 It has all of the above.

[0009] The separator having the above formulas (1) to (3) can reduce the thickness of the separator to an appropriate range when a pressure of 4 MPa, which simulates the expansion pressure of the negative electrode due to repeated charging and discharging, is applied from the thickness direction. This allows the applied pressure to be alleviated. Therefore, a nonaqueous electrolyte secondary battery can be realized in which an increase in the reaction force against the expansion pressure of the electrode assembly due to repeated charging and discharging is reduced. In addition, the separator having the above configuration suppresses changes in the thickness of the separator when assembling the battery pack, thereby improving the assembly stability of the battery pack.

[0010] In a preferred embodiment of the separator disclosed herein, the adhesive layer occupies an area ratio of 40% to 60% of the surface of the substrate on the side where the adhesive layer is provided, which makes it easier for the adhesive layer to spread to the region where no adhesive layer is formed (non-adhesive layer region) when pressure is applied from the thickness direction of the separator, and makes it easier to disperse the pressure in a direction different from the thickness direction, thereby more suitably reducing the pressure.

[0011] In a preferred embodiment of the separator disclosed herein, the average thickness of the adhesive layer on the side of the substrate where the adhesive layer is provided is 2 μm to 3 μm, thereby ensuring the thickness of the adhesive layer that is expanded by pressure from the thickness direction, and making it possible to suitably reduce the pressure.

[0012] In one embodiment of the separator disclosed herein, the adhesive layers may be provided at a predetermined pitch so as to form a stripe pattern. With this configuration, the adhesive layers and the non-adhesive layer regions are alternately arranged, so that when pressure is applied from the thickness direction, the adhesive layers are easily pushed and spread into the non-adhesive layer regions, and the pressure can be suitably reduced.

[0013] The present disclosure also provides a nonaqueous electrolyte secondary battery including an electrode assembly including a positive electrode, a negative electrode, and the separator disclosed herein, and a nonaqueous electrolyte, which realizes a reduction in an increase in reaction force against the expansion pressure of the electrode assembly caused by repeated charging and discharging.

[0014] The present disclosure also provides a battery pack in which a plurality of unit cells are electrically connected to one another and arranged, at least one of the plurality of unit cells being the nonaqueous electrolyte secondary battery disclosed herein. With this configuration, an increase in reaction force against the expansion pressure of the electrode assembly caused by repeated charging and discharging is reduced, thereby realizing a battery pack with improved assembly stability. [Brief description of the drawings]

[0015] [Figure 1] 1 is a cross-sectional view illustrating a schematic configuration of a nonaqueous electrolyte secondary battery according to one embodiment. [Diagram 2] FIG. 2 is an exploded view showing a schematic configuration of an electrode assembly of the nonaqueous electrolyte secondary battery according to one embodiment. [Diagram 3] 1 is a perspective view showing a schematic configuration of a battery pack according to an embodiment; [Figure 4] FIG. 2 is a schematic diagram (top view) of a separator according to one embodiment, as viewed from a direction perpendicular to the surface thereof. [Diagram 5] FIG. 2 is a partial cross-sectional view of a separator according to one embodiment. [Figure 6] FIG. 5 is a partially enlarged view of the vicinity of the long side of FIG. [Figure 7] 1 is a schematic diagram of a separator according to one embodiment when the separator is immersed in an electrolyte solution and a pressure of 1 MPa is applied to the separator in its thickness direction. [Figure 8] 1 is a schematic diagram of a separator according to one embodiment when the separator is immersed in an electrolyte solution and a pressure of 0.5 MPa is applied to the separator in its thickness direction. FIG. [Figure 9] 1 is a schematic diagram of a separator according to one embodiment when the separator is immersed in an electrolyte solution and a pressure of 4 MPa is applied to the separator in its thickness direction. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The technology disclosed herein will be described in detail below. Matters necessary for implementation other than those specifically mentioned in this specification can be understood as design matters for a person skilled in the art based on the prior art in the field. The content of the technology disclosed herein can be implemented based on the content disclosed in this specification and common technical knowledge in the field.

[0017] In addition, each drawing is a schematic drawing, and the dimensional relationship (length, width, thickness, etc.) does not reflect the actual dimensional relationship. In addition, in the drawings described below, the same reference numerals are used for members and parts having the same function, and duplicated explanations may be omitted or simplified. Furthermore, in this specification, when a numerical range is described as "A to B (where A and B are any numerical values)," this means "A or more and B or less," and also encompasses the meanings of "greater than A and less than B," "greater than A and B or less," and "greater than A and less than B."

[0018] In this specification, the term "secondary battery" refers to a general term for an electricity storage device that can be repeatedly charged and discharged, and is a concept that encompasses so-called storage batteries (chemical batteries) such as lithium ion secondary batteries and nickel-metal hydride batteries, and capacitors (physical batteries) such as electric double layer capacitors. In addition, in this specification, the term "lithium ion secondary battery" refers to a secondary battery that uses lithium ions as a charge carrier and realizes charging and discharging by the transfer of charge associated with lithium ions between positive and negative electrodes. Hereinafter, an embodiment of a nonaqueous electrolyte secondary battery 100 in which the separator disclosed herein can be suitably adopted will be described.

[0019] FIG. 1 is a cross-sectional view showing a schematic configuration of a nonaqueous electrolyte secondary battery 100 according to an embodiment. The nonaqueous electrolyte secondary battery 100 is a rectangular sealed battery constructed by accommodating a flat electrode body (wound electrode body) 20 and a nonaqueous electrolyte (not shown) inside a battery case 30. Here, the nonaqueous electrolyte secondary battery 100 is a lithium ion secondary battery. The electrode body 20 is accommodated in the battery case 30 in a state where it is accommodated in an electrode body holder 80 for preventing conduction between the electrode body 20 and the battery case 30. The battery case 30 is provided with a positive electrode terminal 42 and a negative electrode terminal 44 for external connection. In addition, a thin-walled safety valve 36 is provided that is set to release the internal pressure when the internal pressure of the battery case 30 rises to a predetermined level or higher. Furthermore, the battery case 30 is provided with a liquid injection port (not shown) for injecting the nonaqueous electrolyte. The material of the battery case 30 is preferably a metal material that is high in strength, lightweight, and has good thermal conductivity. Such metal materials include, for example, aluminum and steel.

[0020] FIG. 2 is an exploded view showing a schematic configuration of an electrode assembly 20 of a nonaqueous electrolyte secondary battery 100 according to an embodiment. As shown in FIG. 2, the electrode assembly 20 is a wound electrode assembly in which a long sheet-like positive electrode 50 and a long sheet-like negative electrode 60 are stacked with two long sheet-like separators 70 interposed therebetween and wound around a winding axis. The positive electrode 50 includes a positive electrode current collector 52 and a positive electrode mixture layer 54 formed in the longitudinal direction on one or both sides (both sides here) of the positive electrode current collector 52. At one edge of the positive electrode current collector 52 in the winding axis direction (i.e., the sheet width direction perpendicular to the longitudinal direction), a portion where the positive electrode mixture layer 54 is not formed in a strip shape along the edge and the positive electrode current collector 52 is exposed (i.e., a positive electrode current collector exposed portion 52a). The negative electrode 60 includes a negative electrode current collector 62 and a negative electrode mixture layer 64 formed in the longitudinal direction on one or both sides (both sides in this case) of the negative electrode current collector 62. At the edge of the negative electrode current collector 62 on the opposite side of one side in the winding axis direction, a portion where the negative electrode mixture layer 64 is not formed in a strip shape along the edge and the negative electrode current collector 62 is exposed (i.e., a negative electrode current collector exposed portion 62a) is provided. A positive electrode current collector plate 42a is joined to the positive electrode current collector exposed portion 52a, and a negative electrode current collector plate 44a is joined to the negative electrode current collector exposed portion 62a (see FIG. 1). The positive electrode current collector plate 42a is electrically connected to a positive electrode terminal 42 for external connection, and realizes electrical continuity between the inside and the outside of the battery case 30. Similarly, the negative electrode current collector plate 44a is electrically connected to a negative electrode terminal 44 for external connection, and realizes electrical continuity between the inside and the outside of the battery case 30 (see FIG. 1). A current interrupter (CID) may be provided between the positive terminal 42 and the positive current collector plate 42a or between the negative terminal 44 and the negative current collector plate 44a.

[0021] The positive electrode current collector 52 constituting the positive electrode 50 may be, for example, an aluminum foil. The positive electrode mixture layer 54 contains a positive electrode active material. As the positive electrode active material, a known positive electrode active material used in lithium ion secondary batteries may be used, for example, a lithium composite metal oxide having a layered structure, a spinel structure, an olivine structure, or the like (for example, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNiO2, LiCoO2, LiFeO2, LiMn2O4, LiNi0.5 Mn 1.5 Examples of the conductive material include LiCrMnO4, LiCrMnO4, LiFePO4, etc. The positive electrode mixture layer 54 may also include a conductive material, a binder, etc. As the conductive material, for example, carbon black such as acetylene black (AB) or other carbon materials (such as graphite) can be suitably used. As the binder, for example, polyvinylidene fluoride (PVdF) can be used. The positive electrode mixture layer 54 can be formed by dispersing the positive electrode active material and materials (conductive material, binder, etc.) used as necessary in an appropriate solvent (e.g., N-methyl-2-pyrrolidone: NMP) to prepare a paste-like (or slurry-like) composition, applying an appropriate amount of the composition to the surface of the positive electrode current collector 52, and drying it.

[0022] The negative electrode current collector 62 constituting the negative electrode 60 may be, for example, copper foil. The negative electrode mixture layer 64 includes a negative electrode active material. As the negative electrode active material, for example, a carbon material such as graphite, hard carbon, or soft carbon may be used. The negative electrode mixture layer 64 may further include a binder, a thickener, or the like. As the binder, for example, styrene butadiene rubber (SBR) or the like may be used. As the thickener, for example, carboxymethyl cellulose (CMC) or the like may be used. The negative electrode mixture layer 64 can be formed, for example, by dispersing the negative electrode active material and materials (such as a binder) used as necessary in an appropriate solvent (such as ion-exchanged water) to prepare a paste-like (or slurry-like) composition, applying an appropriate amount of the composition to the surface of the negative electrode current collector 62, and drying it.

[0023] The separator disclosed herein is used as the separator 70. Details of the separator will be described later.

[0024] The non-aqueous electrolyte can be the same as that used in conventional lithium ion secondary batteries. For example, a non-aqueous electrolyte containing a supporting salt in an organic solvent (nonaqueous solvent) can be used. As the non-aqueous solvent, aprotic solvents such as carbonates, esters, ethers, etc. can be used. Among them, carbonates, for example, ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), etc., can be preferably used. Alternatively, fluorine-based solvents such as fluorinated carbonates, such as monofluoroethylene carbonate (MFEC), difluoroethylene carbonate (DFEC), monofluoromethyl difluoromethyl carbonate (F-DMC), trifluorodimethyl carbonate (TFDMC), etc. can be preferably used. Such non-aqueous solvents can be used alone or in appropriate combination of two or more. As the supporting salt, for example, lithium salts such as LiPF6, LiBF4, LiClO4, etc. can be preferably used. The concentration of the supporting salt is not particularly limited, but is preferably about 0.7 mol / L or more and 1.3 mol / L or less. In addition, the nonaqueous electrolyte may contain components other than the nonaqueous solvent and supporting salt described above, so long as the effects of the present technology are not significantly impaired. For example, the nonaqueous electrolyte may contain various additives such as a gas generating agent, a film forming agent, a dispersing agent, and a thickening agent.

[0025] The electrode body holder 80 is made of a material that can function as an insulating member. For example, various thermoplastic resins, typically polyolefin resin materials such as polypropylene (PP) and polyethylene (PE), can be used. The shape of the electrode body holder 80 is not particularly limited, but may be, for example, a bag shape with an open top and a bottom.

[0026] The nonaqueous electrolyte secondary battery 100 may further include an elastic body to relieve pressure generated on the electrode assembly 20 due to charging. The elastic body is typically made of an elastically deformable resin material having resistance to a nonaqueous electrolyte. For example, chloroprene rubber, silicone rubber, etc. are preferably used as the resin material. The shape of the elastic body is not particularly limited, but it may typically be a sheet-like elastic body. The elastic modulus of the elastic body may be, for example, 0.5 MPa to 2 MPa. The elastic modulus of the elastic body is measured by a method conforming to JIS K6272.

[0027] FIG. 3 is a perspective view showing a schematic diagram of a battery pack 10 according to an embodiment. As shown in FIG. 3, non-aqueous electrolyte secondary batteries 100 are used as a plurality of single cells constituting the battery pack 10, and the plurality of non-aqueous electrolyte secondary batteries are electrically connected to each other and arranged. The non-aqueous electrolyte secondary batteries 100 are arranged in a mutually arranged manner while being inverted one by one, so that the positive electrode terminals 42 and the negative electrode terminals 44 are arranged alternately in the arrangement direction. A spacer 12 is sandwiched between the arranged non-aqueous electrolyte secondary batteries 100. The spacer 12 can function as a heat dissipation means for efficiently dissipating heat, a length adjustment means, and the like. A pair of end plates (restraint plates) 17 are arranged on both ends of the arranged non-aqueous electrolyte secondary batteries 100. In addition, a tightening beam material 18 is attached so as to bridge between the two end plates 17. The ends of the beam material 18 are tightened and fixed to the end plates 17 by screws 19. As a result, the multiple nonaqueous electrolyte secondary batteries 100 are restrained so that a predetermined restraining load (assembly pressure) is applied in the arrangement direction of the nonaqueous electrolyte secondary batteries 100 (thickness direction of the electrode body 20).

[0028] The battery pack 10 includes a bus bar 14 that connects the positive electrode terminal 42 of one cell (non-aqueous electrolyte secondary battery 100) to the negative electrode terminal 44 of the other cell (non-aqueous electrolyte secondary battery 100) between two adjacently arranged non-aqueous electrolyte secondary batteries 100. This electrically connects the multiple non-aqueous electrolyte secondary batteries 100 to each other. Here, the multiple non-aqueous electrolyte secondary batteries 100 are connected in series, but they may also be connected in parallel. In addition, the single cells that make up the battery pack 10 need only include at least one non-aqueous electrolyte secondary battery 100 disclosed herein, and all the single cells may be composed of the non-aqueous electrolyte secondary batteries 100 disclosed herein.

[0029] The separator 70 disclosed herein will be described below. Fig. 4 is a schematic diagram (top view) of the separator 70 according to one embodiment as viewed from a direction perpendicular to the surface. Fig. 5 is a partial cross-sectional view of the separator 70 according to one embodiment. Fig. 6 is a partial enlarged view of the vicinity of the long side of Fig. 4.

[0030] As shown in Figs. 4 and 5, the separator 70 according to this embodiment includes a substrate 72 made of a porous resin, a heat-resistant layer 74 containing inorganic particles, and an adhesive layer 76 containing an adhesive resin. The separator 70 is in a sheet shape and has a pair of opposing surfaces (main surfaces). In Fig. 4, the MD direction indicated by the arrow is the longitudinal direction of the separator 70, and as shown in Fig. 4, the surface (main surface) of the separator 70 has a long side parallel to the MD direction. In the illustrated example, the separator 70 is elongated so that it can be easily manufactured continuously. However, the separator 70 is not limited to being elongated, and may have any shape, such as a square, polygonal, elliptical, or circular shape, when viewed from above (in a plan view).

[0031] The porous resin constituting the substrate 72 may be a known porous resin having ion permeability and insulating properties and used in separators of non-aqueous electrolyte secondary batteries. Examples of the resin include polyolefin, polyester, cellulose, polyamide, ethylene-propylene copolymer, and the like. Among them, polyolefin is preferable because it can impart a so-called shutdown function to the separator 70. Examples of suitable polyolefin include polyethylene (PE), polypropylene (PP), and the like.

[0032] The substrate 72 may have a single layer structure, or a laminated structure of two or more layers (for example, a three-layer structure in which PP layers are laminated on both sides of a PE layer).

[0033] The thickness of the substrate 72 is not particularly limited as long as it can insulate the positive and negative electrodes, and may be, for example, 1 μm or more and 20 μm or less, preferably 4 μm or more and 15 μm or less, and more preferably 4 μm or more and 12 μm or less, for example, 6 μm or more and 12 μm or less. When the thickness (film thickness) of the substrate 72 is 4 μm or more, a more sufficient strength can be ensured, and the safety of the nonaqueous electrolyte secondary battery is improved. Also, when the thickness of the substrate 72 is 15 μm or less, the distance between the positive and negative electrodes can be narrowed, and better charge and discharge characteristics can be obtained.

[0034] The porosity of the substrate 72 is not particularly limited and may be the same as the porosity of a known substrate layer of a separator for a non-aqueous electrolyte secondary battery. The porosity of the substrate 72 is, for example, 20% to 70%, preferably 30% to 60%, and more preferably 40% to 50%. The porosity of the substrate 72 can be measured by mercury intrusion porosimetry.

[0035] The air permeability of the substrate 72 is not particularly limited and may be the same as the porosity of a known substrate layer of a separator for a nonaqueous electrolyte secondary battery. The air permeability of the substrate 72 is, for example, 50 sec / 100 mL or more and 600 sec / 100 mL or less, preferably 150 sec / 100 mL or more and 300 sec / 100 mL or less, in terms of Gurley value. The Gurley value of the substrate 72 can be measured by a method specified in JIS P8117 (2009).

[0036] 5, in the separator 70 according to this embodiment, the heat-resistant layer 74 is formed on both surfaces in the thickness direction of the substrate 72. However, the heat-resistant layer 74 may be formed arbitrarily, and for example, it may be provided on the surface on one side of the substrate 72, or the heat-resistant layer 74 may not be formed.

[0037] The type of inorganic particles contained in the heat-resistant layer 74 is not particularly limited. Examples of inorganic particles include oxide ceramic particles such as alumina (Al2O3), silica (SiO2), titania (TiO2), zirconia (ZrO2), magnesia (MgO), ceria (CeO2), and zinc oxide (ZnO); nitride ceramic particles such as silicon nitride, titanium nitride, and boron nitride; metal hydroxide particles such as calcium hydroxide, magnesium hydroxide, and aluminum hydroxide; clay mineral particles such as mica, talc, boehmite, zeolite, apatite, and kaolin; sulfate particles such as barium sulfate and strontium sulfate; and glass fibers. Among these, alumina and boehmite particles are preferably used. Alumina and boehmite have a high melting point and excellent heat resistance. In addition, alumina and boehmite have a relatively high Mohs hardness and are also excellent in mechanical strength and durability. Furthermore, alumina and boehmite are relatively inexpensive. Raw material costs can be reduced.

[0038] The shape of the inorganic particles is not particularly limited, and may be, for example, spherical or rectangular columnar. The average particle diameter (D50) of the spherical inorganic particles is not particularly limited, and may be, for example, 0.1 μm to 5 μm, preferably 0.3 μm to 3 μm, and more preferably 0.5 μm to 1.5 μm. In this specification, the average particle diameter (D50) refers to the median diameter (D50), and therefore means a particle diameter corresponding to a cumulative frequency of 50 volume % from the fine particle side having a small particle diameter in a volume-based particle size distribution based on a laser diffraction / scattering method. Therefore, the average particle diameter (D50) can be determined using a known laser diffraction / scattering type particle size distribution measuring device or the like. The average length of one side of the rectangular columnar inorganic particles is preferably 0.1 μm to 1.5 μm, and more preferably 0.5 μm to 1.2 μm. If the inorganic particles are within the above range, a heat-resistant layer 74 having good ion permeability and excellent durability can be formed.

[0039] The heat-resistant layer 74 may contain components other than inorganic particles, examples of which include binders, thickeners, etc. Examples of binders include fluorine-based polymers such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF), acrylic binders, rubber-based binders such as styrene butadiene rubber (SBR), polyolefin-based binders, etc. Examples of thickeners include carboxymethyl cellulose (CMC), methyl cellulose (MC), etc.

[0040] The content of inorganic particles in the heat-resistant layer 74 is not particularly limited, but is preferably 85% by mass to 99.9% by mass, and more preferably 90% by mass to 99.5% by mass. The content of binder in the heat-resistant layer 74 is not particularly limited, but is preferably 0.1% by mass to 15% by mass, and more preferably 0.5% by mass to 10% by mass.

[0041] The average thickness of the heat-resistant layer 74 is not particularly limited, and is, for example, 0.3 μm to 6 μm, preferably 0.5 μm to 4.5 μm, and more preferably 1 μm to 2 μm. The average thickness of the heat-resistant layer 74 refers to the thickness of the heat-resistant layer 74 formed on one surface of the substrate 72. The average thickness of the heat-resistant layer 74 can be measured by observing a cross-sectional SEM image or using a laser microscope.

[0042] The porosity of the heat-resistant layer 74 is not particularly limited and may be the same as that of a known heat-resistant layer 74 of a separator for a non-aqueous electrolyte secondary battery. The porosity of the heat-resistant layer 74 is, for example, 30% or more and 90% or less, preferably 40% or more and 80% or less, and more preferably 50% or more and 70% or less. The porosity of the heat-resistant layer 74 can be measured by mercury intrusion porosimetry.

[0043] The adhesive layer 76 is partially provided on one or both sides in the thickness direction of the substrate 72. In this embodiment, as shown in FIG. 5, the adhesive layer 76 is provided on the surface of the heat-resistant layer 74 on both sides in the thickness direction of the substrate 72. The adhesive layer 76 firmly bonds the separator 70 and the electrodes, so that the inter-electrode distance (i.e., the distance between the positive electrode and the negative electrode) can be kept constant. This makes it possible to suppress the deposition of metallic lithium and the retention of generated gas caused by the non-uniformity of the inter-electrode distance. Therefore, the adhesive layer 76 only needs to be provided on the outermost layer of the separator 70. For example, the adhesive layer 76 may be provided directly on the surface of the substrate 72 without the heat-resistant layer 74.

[0044] In this way, by forming the adhesive layer 76 partially, not on the entire surface of the substrate 72, when a predetermined pressure is applied from the thickness direction of the separator 70, the adhesive layer 76 is pushed and spread to the region where the adhesive layer 76 is not present (the adhesive layer non-formed region 78) (see FIG. 9 described later). This allows the pressure to be dispersed in a direction different from the thickness direction (for example, a direction perpendicular to the thickness direction), and the pressure from the thickness direction to be reduced (alleviated). Therefore, as the nonaqueous electrolyte secondary battery 100 is repeatedly charged and discharged, the film thickness (volume) of the negative electrode 60 increases, and the expansion pressure of the electrode assembly 20 increases, but by using the separator 70 disclosed herein, such expansion pressure can be alleviated. In other words, the reaction force against the expansion pressure of the electrode assembly 20 can be reduced.

[0045] On the side of the substrate 72 on which the adhesive layer 76 is provided, the surface area ratio of the adhesive layer 76 to the surface of the substrate 72 may be, for example, 35% or more and less than 85%, preferably 40% or more and 80% or less, for example 40% or more and 60% or less. If the surface area ratio of the adhesive layer 76 is 35% or more, the adhesive strength between the separator 70 and the electrode can be sufficiently ensured. Also, if the surface area ratio of the adhesive layer 76 is less than 85%, the area (adhesive layer non-formed area 78) where the adhesive layer 76 can be pushed out when pressure is applied from the thickness direction of the separator 70 becomes wider, so that the expansion pressure of the electrode body 20 due to charging can be suitably alleviated.

[0046] As an example of the formation pattern of the adhesive layer 76, in this embodiment, the adhesive layer 76 is provided at a predetermined pitch so as to be formed in a stripe pattern. Therefore, as shown in the figure, the adhesive layer 76 is formed as a convex portion extending in one direction, and an adhesive layer non-formed region is formed as a concave portion between adjacent adhesive layers 76. In other words, on the surface of the separator 70 on which the adhesive layer 76 is provided, a region having the adhesive layer 76 and a region without the adhesive layer 76 (adhesive layer non-formed region 78) are alternately formed. By alternately forming the adhesive layer 76 and the adhesive layer non-formed region 78 in this way, when pressure is applied from the thickness direction of the separator 70, the adhesive layer 76 can be pushed and spread to the adhesive layer non-formed region 78 adjacent to both sides, so that the pressure applied can be suitably reduced. Note that it is acceptable that the adhesive layer non-formed region 78 has a small amount of adhesive component attached thereto due to technical limitations in manufacturing (for example, the coverage rate of the adhesive component in the adhesive layer non-formed region 78 is 5% or less, preferably 1% or less).

[0047] In this embodiment, the stripe pattern of the adhesive layer 76 is formed as an oblique stripe pattern. The adhesive layer 76 and the long side of the surface of the separator 70 are formed to form an acute angle (i.e., the angle θ shown in FIG. 6 is 0°<θ<90°). From the viewpoint of the injectability of the electrolyte, the angle θ between the adhesive layer 76 and the long side of the surface of the separator 70 may be, for example, 20° to 70°, preferably 30° to 65°, and more preferably 45° to 60°. Here, the adhesive layer 76 is formed as an oblique stripe pattern, but the stripe pattern may be parallel or perpendicular to the long side of the surface of the separator 70.

[0048] The width of the adhesive layer 76 (i.e., the dimension perpendicular to the extension direction of the adhesive layer 76; dimension W shown in FIG. 6) is not particularly limited, but is, for example, 1 mm or more and 4 mm or less, preferably 2 mm or more and 4 mm or less, for example, 2 mm or more and 3 mm or less.

[0049] The distance between adhesive layers 76 (ie, the width of the gap between adhesive layers 76; dimension P shown in FIG. 6) is not particularly limited, but is, for example, 1 mm or more and 4 mm or less, and preferably 2 mm or more and 3 mm or less.

[0050] The average thickness of the adhesive layer 76 (i.e., the dimension in the direction perpendicular to the surface of the separator 70) is preferably 1 μm or more and less than 4 μm, more preferably 1 μm or more and 3 μm or less, and more preferably 2 μm or more and 3 μm or less. By making the average thickness of the adhesive layer 76 1 μm or more, when pressure is applied from the thickness direction of the separator 70, the adhesive layer 76 is easily pushed and spread toward the adhesive layer non-forming region 78, and the pressure can be suitably relaxed. In addition, by making the average thickness of the adhesive layer 76 less than 4 μm, the diffusibility of lithium ions during charging of the nonaqueous electrolyte secondary battery 100 can be increased, and excellent battery characteristics can be ensured. The thickness of the adhesive layer 76 can be measured by cross-sectional SEM image observation or a laser microscope.

[0051] In a suitable example of the separator 70 having the adhesive layer 76 in a stripe pattern, the average thickness of the adhesive layer 76 is 2 μm to 3 μm, the width of the adhesive layer 76 is 2 mm to 3 mm, and the distance between the adhesive layers 76 is 2 mm to 3 mm. By providing all of these, pressure from the thickness direction can be alleviated to an especially high level.

[0052] 5, the adhesive layer 76 has a rectangular cross section. The rectangular cross section of the adhesive layer 76 makes it easy to obtain a large adhesive area with the electrode. However, the cross-sectional shape of the adhesive layer 76 is not limited thereto as long as it can bond the electrode and the separator 70.

[0053] The adhesive layer 76 contains an adhesive component. The type of adhesive component is not particularly limited as long as it can bond the electrodes and the separator 70. The adhesive component is typically an adhesive resin, and examples thereof include polyvinylidene fluoride (PVdF); diene rubbers such as styrene butadiene rubber (SBR), acrylonitrile-butadiene rubber (NBR), and acrylonitrile-butadiene-styrene rubber (NSBR); (meth)acrylic resins such as polyacrylic acid, butyl acrylate-ethylhexyl acrylate copolymer, and methyl methacrylate-ethylhexyl acrylate copolymer; cellulose derivatives such as carboxymethyl cellulose and hydroxyalkyl cellulose; polyacrylonitrile; polyvinyl chloride; polyvinyl alcohol; polyvinyl butyral; and polyvinylpyrrolidone. The adhesive layer 76 may contain one type of these adhesive resins alone, or may contain two or more types. Among these, polyvinylidene fluoride (PVdF) is preferred from the viewpoints of high adhesion between the separator and electrodes and prevention of adverse effects on battery characteristics.

[0054] The adhesive layer 76 may contain only the adhesive component, or may further contain components other than the adhesive component (in other words, other components). Examples of other components include additives such as inorganic particles, antifoaming agents, surfactants, wetting agents, antifoaming agents, and pH adjusters. For example, when the adhesive layer 76 contains inorganic particles, the heat resistance of the separator 70 can be improved. As the inorganic particles, for example, those exemplified as the inorganic particles that may be contained in the heat-resistant layer 74 described above can be used. When the adhesive layer 76 contains inorganic particles, the ratio of the inorganic particles in the entire adhesive layer 76 is preferably 40 wt% or less, and preferably 30 wt% or less.

[0055] When the adhesive layer 76 contains a component other than the adhesive component, the ratio of the adhesive component in the entire adhesive layer 76 is 60 wt% or more, preferably 70 wt% or more, for example, 80 wt% or more, or 90 wt% or more, thereby ensuring the adhesiveness of the adhesive layer 76.

[0056] In the illustrated example, the separator 70 has only three types of layers: the substrate 72, the heat-resistant layer 74, and the adhesive layer 76. However, the separator 70 may further have layers other than the substrate 72, the heat-resistant layer 74, and the adhesive layer 76, as long as the effects of the present technology are not significantly impaired.

[0057] Hereinafter, the parameters related to the thickness of the separator 70 disclosed herein will be described. Fig. 7 is a schematic diagram of the separator 70 when the separator 70 is immersed in an electrolytic solution and a pressure of 1 MPa is applied from the thickness direction of the separator 70. Fig. 8 is a schematic diagram of the separator 70 when the separator 70 is immersed in an electrolytic solution and a pressure of 0.5 MPa is applied from the thickness direction of the separator 70. Fig. 9 is a schematic diagram of the separator 70 when the separator 70 is immersed in an electrolytic solution and a pressure of 4 MPa is applied from the thickness direction of the separator 70.

[0058] As shown in FIG. 5, the initial thickness T0 of the separator 70 is the thickness of the separator 70 before impregnation with the nonaqueous electrolyte. The initial thickness T0 of the separator 70 is, for example, 2 μm or more and 30 μm or less, preferably 10 μm or more and 22.5 μm or less, more preferably 16 μm or more and 22.5 μm or less, and even more preferably 19 μm or more and 22.5 μm or less. When the initial thickness T0 of the separator is 10 μm or more, a more sufficient strength can be ensured, and the safety of the nonaqueous electrolyte secondary battery is improved. In addition, when the initial thickness T0 of the separator is 22.5 μm or less, the distance between the positive and negative electrodes can be narrowed, and better charge and discharge characteristics can be obtained. The initial thickness T0 of the separator 70 is measured in accordance with JIS standard Z1702.

[0059] As shown in FIG. 7, the separator 70 is impregnated with an electrolytic solution, and a pressure of 1 MPa is applied to the separator 70 from the thickness direction of the separator 70. The thickness T1 of the separator 70 is, for example, 10 μm to 25 μm, preferably 16 μm to 24 μm, and more preferably 20 μm to 24 μm. By impregnating the separator 70 with the electrolytic solution, the electrolytic solution permeates the porous separator, and the electrolytic solution 90 also permeates the adhesive layer non-formation region 78. In FIG. 7, the separator 70 is sandwiched between the first pressurizing element 110 and the second pressurizing element 120 in the thickness direction, and a pressure of 1 MPa is applied to the separator 70. The first pressurizing element 110 and the second pressurizing element 120 are illustrated to explain the state of the separator 70 when pressure is applied, and do not affect the content of the present technology. The thickness T1 of the separator 70 indicates the thickness when simulating a state in which the nonaqueous electrolyte secondary battery is injected with an electrolyte and assembled as a single cell constituting a battery pack. The thickness T1 of the separator 70 and thicknesses T2 and T4 described later can be measured by impregnating a plurality of test pieces of the separator 70 (50 or more, for example, 150 pieces) in a stacked state with the electrolyte, and then applying pressure using a commercially available autograph device. A specific measurement method will be shown in the test example described later.

[0060] When the separator 70 is impregnated with the electrolyte, the electrolyte may penetrate into the separator 70, causing swelling of the separator 70 (particularly swelling of the adhesive layer 76), or a liquid phase or gas phase of the electrolyte 90 may occur on the surface of the separator 70 (between the surface of the separator 70 and the layer adjacent thereto). As a result, the thickness T1 of the separator 70 tends to be greater than the initial thickness T0. Therefore, the value (T1 / T0) obtained by dividing the thickness T1 of the separator 70 by the initial thickness T0 of the separator 70 is preferably 1 or more and 1.1 or less, more preferably 1 or more and 1.05 or less. If T1 / T0 is 1 or more, the pair of restraining plates can be stably restrained without narrowing the plate interval of the pair of restraining plates too much during assembly of the battery pack. Also, if T1 / T0 is 1.1 or less, the amount of gas trapped between the separator 70 and the layer adjacent thereto can be suppressed.

[0061] After impregnating the separator 70 with the electrolyte, the separator 70 is subjected to a pressure of 2 MPa from the thickness direction of the separator 70 for 1 hour, and then the pressure is reduced to 0.5 MPa. The thickness T2 of the separator 70 is preferably smaller than the thickness T1 of the separator 70. The thickness T2 of the separator 70 imitates the thickness of the separator after the first charge and discharge after the assembled battery is assembled. Specifically, the state in which the pressure of 2 MPa is applied for 1 hour imitates the pressure on the separator caused by the expansion of the negative electrode due to charging, and the state in which the pressure is reduced to 0.5 MPa imitates the state after discharging, which imitates the pressure on the separator caused by the negative electrode whose volume has increased due to the first charge and discharge. That is, the thickness T2 of the separator 70 imitates the thickness when the above-mentioned BOL reaction force is generated. If the BOL reaction force is too small, the assembly stability of the battery pack will deteriorate, so the separator is required not to excessively ease the expansion pressure of the electrode body when the BOL reaction force is generated. Therefore, it is preferable that the thickness T2 of the separator 70 is not too small compared to the thickness T1. Therefore, the value (T2 / T1) obtained by dividing the thickness T2 of the separator 70 by the thickness T1 is preferably 0.92 or more and 1 or less, more preferably 0.94 or more and 1 or less, and even more preferably 0.95 or more and 1 or less. By making T2 / T1 1 or less, it is possible to ensure the escape of gas generated during initial charge and discharge.

[0062] After the operation for measuring the thickness T2, a pressure of 4 MPa is applied to the separator 70 from the thickness direction of the separator 70, and the pressure is maintained for 48 hours. The thickness T4 of the separator 70 when the pressure is maintained is determined as T4. The value (T4 / T1) obtained by dividing the thickness T4 by the thickness T1 is preferably 0.6 to 0.8, more preferably 0.7 to 0.77, and even more preferably 0.74 to 0.77. The thickness T4 is a simulation of the thickness of the separator in a state in which the separator is pressed by the negative electrode with an increased thickness after repeatedly charging and discharging the assembled battery (non-aqueous electrolyte secondary battery). If the expansion pressure that increases due to repeated charging and discharging cannot be sufficiently alleviated, deterioration of the battery performance and shortening of the battery life are likely to occur, and there is a risk of a decrease in safety. Therefore, by making T4 / T1 0.8 or less, the expansion pressure of the negative electrode can be suitably alleviated, and higher safety can be ensured. 9, when pressure (here, 4 MPa) is applied from the thickness direction, the separator 70 disclosed herein can suitably relieve the pressure by spreading the adhesive layer 76 into the adhesive layer non-formed region 78. Furthermore, since T4 / T1 is 0.6 or more, the amount of thickness change of the separator 70 is suppressed and unevenness in the thickness of the separator 70 is suppressed, so that the inter-electrode distance can be kept relatively uniform. This allows the inter-electrode resistance to be made relatively uniform, so that stable charge / discharge characteristics can be obtained.

[0063] The separator 70 can be manufactured according to a known method. As an example of manufacturing the separator 70 shown in the figure, for example, first, a sheet-shaped porous resin substrate that will become the substrate 72 is prepared. The porous resin substrate is preferably a long substrate. A slurry for forming a heat-resistant layer containing inorganic particles is applied to this porous resin substrate, and then dried to obtain a laminate on which the heat-resistant layer 74 is formed.

[0064] Next, a coating liquid containing an adhesive component and a solvent is prepared and applied to the laminate. In this embodiment, the coating liquid is applied to the laminate at a predetermined pitch so as to form a stripe pattern. Such application can be performed, for example, by using a roll coater equipped with a gravure roll having grooves oblique to the rotation direction.

[0065] The applied coating liquid is dried to form the adhesive layer 76, thereby obtaining the separator 70. Note that the method for producing the separator 70 is not limited to this.

[0066] The configuration of the separator 70 according to one embodiment, and the configurations of the nonaqueous electrolyte secondary battery 100 and the battery pack 10 have been described above. The separator 70 is suitably used in lithium ion secondary batteries. Lithium ion secondary batteries can be used for a variety of purposes. Specific uses include portable power sources for personal computers, portable electronic devices, portable terminals, etc.; power sources for driving vehicles such as electric vehicles (BEVs), hybrid vehicles (HEVs), plug-in hybrid vehicles (PHEVs), etc.; and storage batteries for small power storage devices, etc., and among these, power sources for driving vehicles are preferred.

[0067] As an example, a rectangular nonaqueous electrolyte secondary battery 100 including a flat wound electrode assembly 20 has been described. However, the nonaqueous electrolyte secondary battery disclosed herein can also be configured as a nonaqueous electrolyte secondary battery including a laminated electrode assembly (i.e., an electrode assembly in which multiple positive electrodes and multiple negative electrodes are alternately laminated). The laminated electrode assembly may include multiple separators such that one separator is interposed between each of the positive and negative electrodes, or may be one in which positive electrodes and negative electrodes are alternately laminated with one separator folded back.

[0068] The nonaqueous electrolyte secondary battery disclosed herein can also be configured as a coin battery, a button battery, a cylindrical battery, a laminated case battery, etc. The nonaqueous electrolyte secondary battery disclosed herein can also be configured as a nonaqueous electrolyte secondary battery other than a lithium ion secondary battery according to a known method.

[0069] In the above embodiment, the adhesive layer 76 is formed in a stripe pattern, but the pattern of the adhesive layer 76 is not limited thereto. The adhesive layer 76 may be formed partially on the outermost layer of the separator. In particular, it is preferable that the adhesive layer 76 is formed intermittently, and for example, it is preferable that the adhesive layer 76 and the non-adhesive layer region 78 are alternately arranged multiple times (for example, two or more times). This increases the direction in which the adhesive layer 76 can be pushed out toward the non-adhesive layer region 78 when pressure is applied, so that the pressure can be suitably relaxed. Examples of such patterns of the adhesive layer 76 include a dot pattern and a lattice pattern.

[0070] Hereinafter, examples of the present technology will be described. Note that the present technology is not limited to the following examples.

[0071] [Making the separator] <Example 1> A polyethylene porous film having a thickness of 12 μm was prepared as a substrate. In addition, a slurry containing, as a main component, quadrangular prism-shaped boehmite particles having an average side length of 0.5 μm (85% by mass or more of boehmite particles) was prepared to form a heat-resistant layer. The slurry was applied to both sides of the substrate and dried to form a heat-resistant layer on the substrate. The thickness of the formed heat-resistant layer was 2 μm per side.

[0072] Next, a coating liquid for forming an adhesive layer was prepared by dissolving polyvinylidene fluoride (PVdF) in N-methyl-2-pyrrolidone (NMP). This coating liquid was applied to the surface of the heat-resistant layer on both sides of the substrate formed above in a striped pattern by a printing method, and dried to form an adhesive layer. Specifically, the adhesive layer was applied so that the thickness was 1 μm, the stripe shape was the width of the adhesive layer (width of the stripe), the width of the gap of the adhesive layer (width of the part where the adhesive layer is not formed) was 1 mm, and the angle with respect to the longitudinal direction of the separator was 45°. In this way, the separator of Example 1 was produced.

[0073] <Example 2> A separator of Example 2 was produced in the same manner as in Example 1, except that the thickness of the adhesive layer was 2 μm, the width of the adhesive layer was 3 mm, and the gap width of the adhesive layer was 2 mm. <Example 3> The separator of Example 3 was produced in the same manner as in Example 1, except that the thickness of the adhesive layer was 3 μm, the width of the adhesive layer was 2 mm, and the gap width of the adhesive layer was 3 mm. <Example 4> A separator of Example 4 was produced in the same manner as in Example 1, except that the thickness of the adhesive layer was 3 μm. <Example 5> A separator of Example 5 was produced in the same manner as in Example 1, except that a heat-resistant layer was provided on only one side of the substrate. An adhesive layer was formed on the surface of the substrate on the side on which the heat-resistant layer was not formed. <Example 6> A separator of Example 6 was produced in the same manner as in Example 3, except that a heat-resistant layer was provided on only one side of the substrate. An adhesive layer was formed on the surface of the substrate on the side on which the heat-resistant layer was not formed. <Example 7> A separator of Example 7 was produced in the same manner as in Example 2, except that no heat-resistant layer was provided and adhesive layers were provided on both sides of the substrate. <Example 8> A separator of Example 8 was produced in the same manner as in Example 1, except that a 6 μm-thick porous polyethylene film was used as the substrate and the heat-resistant layer was made to have a thickness of 1 μm. <Example 9> A coating liquid for forming an adhesive layer was prepared by mixing PVdF and quadrangular columnar boehmite particles with an average side length of 0.5 μm in NMP at a mass ratio of 70:30. Using this coating liquid for forming an adhesive layer, an adhesive layer was formed on both sides of a substrate on which a heat-resistant layer was not formed. The adhesive layer was formed to have the same pattern as the stripe pattern of the adhesive layer in Example 1. A separator in Example 9 was produced in the same manner as in Example 1 except for this.

[0074] <Examples 10 and 11> Separators of Examples 10 and 11 were produced in the same manner as in Example 1, except that the adhesive layer was formed on the entire surface of the heat-resistant layer. That is, the adhesive layer was formed as a flat layer having no gaps between the adhesive layers (so-called a solidly coated layer). <Examples 12 and 13> Separators of Examples 12 and 13 were produced in the same manner as in Example 1, except that the thickness of the adhesive layer was 0.5 μm. <Examples 14 and 15> Separators of Examples 14 and 15 were produced in the same manner as in Example 8, except that the adhesive layer was formed on the entire surface of the heat-resistant layer. That is, the adhesive layer was formed as a flat layer having no gaps between the adhesive layers (so-called a solidly coated layer). <Examples 16 and 17> Only the substrate of Example 1 was used as the separator in Examples 16 and 17.

[0075] [Measurement of adhesive layer coating area occupancy rate] The separator surface was observed using a Keyence optical microscope (model number: VHX-600) to determine the coating surface area occupancy rate of the adhesive layer relative to the substrate surface. Specifically, the entire separator was observed at a magnification that allowed the average area occupancy rate to be determined, the color shading of the observed image was binarized to determine the coating area, and then this was divided by the area of ​​the entire observed image to determine the area occupancy rate of the adhesive layer. The results are shown in Table 1.

[0076] [Measurement of adhesive layer coating height (thickness)] The coating height (thickness) of the adhesive layer in each of the above examples was measured from a cross-sectional SEM image. The average height of the adhesive layer was measured based on the average boundary line between the adhesive layer and the substrate (or heat-resistant layer) obtained from the cross-sectional SEM image.

[0077] [Measurement of separator thickness and separator film thickness including liquid phase] In each example, the initial thickness T0 of the separator produced above was measured by a measurement method conforming to JIS standard Z1702 using a constant pressure thickness measuring instrument PG-02J manufactured by Tecrock Corporation. Specifically, 10 samples were prepared by stacking three separators produced above. The samples were placed on a stone surface plate, and the film thickness was measured when a measuring probe with a diameter of 5 mm was pressed against the sample with a pressure of 1.22 N, and the film thickness was measured at three points per sample. The average value of the total 30 film thickness data thus obtained was calculated, and then the thickness T0 was calculated by converting it into the separator film thickness per sheet.

[0078] Next, in each example, 150 sheets of the separators manufactured above were stacked, cut to a width of 80 mm and a length of 150 mm, and sealed in a laminated bag (model number: AL-18) manufactured by Seizo Nipponsha. After injecting 54 mL of electrolyte into the laminated bag, the opening of the laminated bag was sealed by heat welding to prepare a sample. The sample was left overnight and then placed on an aluminum block with a width of 150 mm and a depth of 83.5 mm. At this time, the longitudinal direction of the sample and the longitudinal direction of the aluminum block were set at right angles. Next, a predetermined pressure was applied to the thickness direction (lamination direction) of the sample using an autograph device manufactured by Shimadzu Corporation (model number: AG-50kNX) based on the first pressure application program and the second pressure application program described below, to obtain a stress-strain curve. The area of ​​the sample to which pressure was applied was 80 mm x 83.5 mm. The first and second pressure application programs and the thicknesses (total thickness of the liquid phase and the separator) T1, T2, and T4 of the sample under predetermined pressure conditions are shown below.

[0079] In the first pressure application program, the pressure was increased to a target pressure of 12512N (corresponding to 2MPa) at a speed of 104N / sec, and the target pressure was maintained for 1 hour, after which the pressure was reduced to 300N at a speed of 104N / sec. From the obtained stress-strain curve, the jig distortion of the autograph device and the thickness distortion of the laminate were corrected to obtain the film thickness change of 150 separators. The obtained result was divided by 150 to obtain the thickness per separator. In the above operation, the separator thickness when the pressure reached 1MPa during the pressure increase was defined as T1, and the separator thickness when the pressure reached 0.5MPa during the pressure reduction was defined as T2.

[0080] Next, the sample after the application based on the first pressure application program was subjected to application based on the second pressure application program. In the second pressure application program, the pressure was increased to a target pressure of 25024 N (equivalent to 4 MPa) at a speed of 104 N / sec, and the target pressure was maintained for 48 hours, and then the pressure was reduced to 300 N at a speed of 104 N / sec. The thickness of the separator immediately after maintaining the target pressure for 48 hours (before reducing the pressure) was designated as T4.

[0081] From the thickness values ​​T0, T1, T2, and T4 obtained as described above, T1 / T0, T2 / T1, and T4 / T1 were calculated. Table 1 shows the thickness values ​​T0, T1, T2, and T4, and the values ​​of T1 / T0, T2 / T1, and T4 / T1.

[0082] [Table 1]

[0083] [Preparation of positive electrode] LiNi as a positive electrode active material 0.55 Co 0.20 Mn 0.2597 parts by mass of lithium composite metal oxide represented by O2, 2 parts by mass of acetylene black (AB) as a conductive material, and 1 part by mass of polyvinylidene fluoride (PVdF) as a binder were mixed, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry was applied to both sides of a positive electrode current collector made of aluminum foil, and the coating was dried. After rolling the coating film using a roller, it was cut to a predetermined electrode size, and a positive electrode in which a positive electrode mixture layer was formed on both sides of the positive electrode current collector was produced.

[0084] [Preparation of negative electrode] Next, 98.7 parts by mass of graphite powder as a negative electrode active material, 0.7 parts by mass of carboxymethyl cellulose (CMC) as a thickener, and 0.6 parts by mass of styrene butadiene rubber (SBR) as a binder were mixed, and an appropriate amount of water was added to prepare a negative electrode mixture slurry. Next, the negative electrode mixture slurry was applied to both sides of a negative electrode current collector made of copper foil, and the coating was dried. After rolling the coating film using a roller, it was cut into a predetermined electrode size, and a negative electrode in which a negative electrode mixture layer was formed on both sides of the negative electrode current collector was produced.

[0085] [Preparation of non-aqueous electrolyte] Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) were mixed in a volume ratio of 3:3:4. LiPF6 was dissolved in the mixed solvent at a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.

[0086] [Preparation of test batteries] The positive electrode and the negative electrode were alternately laminated with a separator interposed therebetween to prepare a laminated electrode body. The thickness (length in the lamination direction) of the electrode body was 22.8 mm, the width of the housing part of the electrode body holder in which the electrode body was housed was 24.5 mm, and the inner dimension in the short side direction of the rectangular box-shaped battery case (case body) in which the electrode body holder in which the electrode body was housed was 24.8 mm. Next, the electrode body was housed in the electrode body holder in a state in which it was sandwiched between non-foamed elastic sheets composed mainly of chloroprene rubber having a thickness of 0.47 mm and an elastic modulus of 1.5 MPa from both sides in the lamination direction, and the electrode body holder was further housed in the case body. After that, the non-aqueous electrolyte was injected into the case body. The injection of the non-aqueous electrolyte was performed in a non-aqueous environment with the case body pressed so that pressure was applied from both sides in the lamination direction of the electrode body. Next, the lead portions (exposed portions of the current collector) of each electrode were connected to the positive and negative terminals provided on the sealer, respectively, and the opening of the case body was closed with the sealer to prepare a rectangular test battery.

[0087] [Initial capacity measurement] The test battery was charged at a constant current of 21.5 A up to 4.25 V, and then charged at a constant voltage of 3 A. It was then discharged at a constant current of 21.5 A down to 2.5 V, and the discharge capacity at this time was taken as the initial capacity. Next, the BOL reaction force and the EOL reaction force (End of life reaction force) of the test battery were measured by the following method.

[0088] [Measurement of BOL and EOL reaction forces] After the initial capacity was confirmed, the test battery was discharged until the SOC (state of charge) was 0%, and then the test battery was sandwiched between two SUS plates (140 mm x 75 mm) so that pressure was applied from both sides of the stacking direction of the electrode body, and a load mutation curve was obtained using a universal testing machine AG-Xplus manufactured by Shimadzu Corporation. First, the distance between the two SUS plates was brought closer to the test battery, and pressure was applied so that the load mutation curve showed a specified pressure (see Table 2). The pressure at this time is shown in Table 2 as the assembly pressure. After that, the battery was charged at a constant current of 21.5 A to 4.25 V, and then charged at a constant voltage of 3 A. The pressure shown by the load mutation curve when the battery was discharged at a constant current of 21.5 A to 2.5 V was taken as the BOL reaction force. Next, the test battery was repeatedly charged and discharged under the above charge and discharge conditions until the capacity of the test battery reached 70% of the initial capacity. The EOL reaction force was determined as the pressure indicated by the load deformation curve when constant current discharge was performed in the charge-discharge cycle in which the capacity of the test battery reached 70% of the initial capacity. The BOL reaction force and EOL reaction force for each example are shown in Table 2.

[0089] [Evaluation of BOL reaction force] The higher the BOL reaction force, the less likely the battery will fall off the restraining member after assembling a plurality of single cells to manufacture a battery pack and charging and discharging the battery pack. Therefore, the higher the BOL reaction force, the better. Here, the BOL reaction force is marked as "x" when it is less than 0.3 MPa, "good" when it is 0.3 MPa or more, and "great" when it is 0.5 MPa or more.

[0090] [EOL reaction force evaluation] The smaller the EOL reaction force, the smaller the increase in the expansion pressure of the electrode body (negative electrode) caused by charging and discharging the battery. Therefore, the lower the EOL reaction force, the better. Here, the EOL reaction force is marked with "x" when it is 3 MPa or more, "o" when it is less than 3 MPa, and "◎" when it is 2.5 MPa or less.

[0091] [comprehensive evaluation] When both the BOL reaction force evaluation and the EOL reaction force evaluation were "◎", when either one of the BOL reaction force evaluation and the EOL reaction force evaluation was "〇" and the other was "〇" or "◎", it was marked as "〇", and when at least one of the BOL reaction force evaluation and the EOL reaction force evaluation was "×", it was marked as "×". The results are shown in Table 2.

[0092] [Table 2]

[0093] As shown in Table 2, in Examples 1 to 9, both high BOL reaction force and reduced EOL reaction force were achieved. That is, in Examples 1 to 9, the increase in the expansion pressure of the electrode body due to repeated charging and discharging can be reduced, and high assembly stability can be maintained. As shown in Table 1, the separators in Examples 1 to 9 have the following formulas (1) to (3): (1) 1≦T1 / T0≦1.1 (2) 0.92≦T2 / T1≦1 (3) 0.6≦T4 / T1≦0.8 It can be seen that both of these are provided.

[0094] It can also be seen that it is possible to achieve both high BOL reaction force and reduced EOL reaction force even when the heat-resistant layer is formed on only one side of the substrate as in Examples 5 and 6, when there is no heat-resistant layer as in Example 7, and when the adhesive layer contains inorganic particles as in Example 9.

[0095] On the other hand, in Examples 10, 11, 14, and 15, the adhesive layer was formed on the entire surface of the heat-resistant layer, and in this case, when the assembly pressure was increased to ensure the BOL reaction force, the reduction in the EOL reaction force was insufficient. Also, as in Examples 16 and 17, even when the adhesive layer was not provided, when the assembly pressure was increased to ensure the BOL reaction force, the reduction in the EOL reaction force was insufficient. Therefore, it can be seen that unless the adhesive layer is at least partially formed, it is not possible to reduce the increase in the expansion pressure of the electrode body due to repeated discharges and to achieve high assembly stability. Also, from the results of Examples 12 and 13, it can be seen that even if the adhesive layer is formed in a stripe pattern, the reduction in the EOL reaction force is insufficient because the above formula (3) is not met.

[0096] Although specific examples of the technology disclosed herein have been described in detail above, these are merely examples and do not limit the scope of the claims. The technology disclosed herein includes various modifications and variations of the above specific examples. [Explanation of symbols]

[0097] 10 Battery pack 20 Electrode body 30 Battery case 36 Safety valve 42 Positive terminal 42a Positive current collector 44 Negative terminal 44a Negative current collector plate 50 positive electrode 52 Positive electrode current collector 52a Exposed part of positive electrode current collector 54 Positive electrode mixture layer 60 negative electrode 62 Negative electrode current collector 62a Exposed part of negative electrode current collector 64 Negative electrode mixture layer 70 Separator 72 Base material 74 Heat-resistant layer 76 Adhesive layer 78 Adhesive layer non-formation area 80 Electrode holder 90 Electrolyte 100 Nonaqueous electrolyte secondary battery 110 First pressure element 120 Second pressure element

Claims

1. A long sheet-like separator for use in a wound electrode body, comprising a sheet-like substrate made of a porous resin and an adhesive layer containing an adhesive resin, The adhesive layer is partially provided on one or both sides in a thickness direction of the base material, The initial thickness of the separator is T0. The separator is impregnated with an electrolyte, and a pressure of 1 MPa is applied to the separator in the thickness direction of the separator. The thickness of the separator is defined as T1. Thereafter, a pressure of 2 MPa was continuously applied to the separator from the thickness direction of the separator for 1 hour, and then the pressure was reduced to 0.5 MPa, and the thickness of the separator was defined as T2, and Further, after that, a pressure of 4 MPa was applied to the separator from the thickness direction of the separator, and the pressure was maintained for 48 hours. The thickness of the separator when this pressure was maintained was defined as T4. The following formulas (1) to (3): (1) 1≦T1 / T0≦1.1 (2) 0.92≦T2 / T1≦1 (3) 0.6≦T4 / T1≦0.8 It has all of the above. The adhesive layer has a width of 1 mm or more and 4 mm or less and an average thickness of 1 μm or more and 3 μm or less, and is provided at a predetermined pitch so as to form a stripe pattern extending at an acute angle to the long side of the separator in a plan view.

2. 2. The separator according to claim 1, wherein an area ratio of the adhesive layer to the surface of the substrate on the side of the substrate on which the adhesive layer is provided is 40% or more and 60% or less.

3. 3. The separator according to claim 1, wherein the average thickness of the adhesive layer on the side of the substrate where the adhesive layer is provided is 2 μm or more and 3 μm or less.

4. A heat-resistant layer containing inorganic particles at a content of 85% by mass or more and 99.9% by mass or less is provided on the base material, the adhesive layer is partially provided on the heat-resistant layer on one or both sides in a thickness direction of the base material, 2. The separator according to claim 1, wherein an area ratio of the adhesive layer to the surface of the substrate on the side where the adhesive layer is provided is 40% or more and 80% or less.

5. A non-aqueous electrolyte secondary battery comprising: an electrode assembly comprising a positive electrode, a negative electrode, and the separator according to any one of claims 1 to 4; and a non-aqueous electrolyte.

6. A battery pack in which a plurality of unit cells are electrically connected to each other and arranged, 6. A battery pack, wherein at least one of the plurality of single cells is the nonaqueous electrolyte secondary battery according to claim 5.

Citation Information

Patent Citations

  • Membrane and electrochemical device comprising same

    CN111224047A

  • Diaphragm as well as preparation method and application thereof

    CN113782915A

  • Method of electromagnetically stirring molten metal

    JP1978028034A

  • Safety system for triaxial satellite

    JP1982099499A

  • Partially coated separator

    JP2001118558A